The Writing of Natural Disaster in Europe, 1500–1826
IX, 182 p. 1 illus.
Keywords: This book explores reactions to and representations of natural disasters in early modern Europe. The contributors illustrate how the cultural production of the period - in manuals, treatises, sermons, travelogues and fiction - grappled with environmental catastrophe. Crucially, they interrogate how people in the early modern era rationalized and mediated the threat of events like plagues, great frosts, storms, floods and earthquakes. A vital contribution to environmental history, this book highlights the parallels between early modern responses to natural disaster and climate anxiety in our own era. Sandhya Patel is Senior Lecturer in Eighteenth-Century Studies at Université Clermont Auvergne, France. Sophie Chiari-Lasserre is Professor of Early Modern English Literature at Université Clermont Auvergne, France.